2011
DOI: 10.1002/jwmg.147
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of activity and fatality of migratory bats at a wind energy facility in Alberta, Canada

Abstract: Studying migratory behavior of bats is challenging. Thus, most information regarding their migratory behavior is anecdotal. Recently, however, fatalities of migratory bats at some wind energy facilities across North America have provided the opportunity and impetus to study bat migration at fine spatial and temporal scales. Using acoustic monitoring and carcass searches, we examined temporal and spatial variation in activity levels and fatality rates of bats at a wind energy facility in southern Alberta, Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
92
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 52 publications
12
92
1
Order By: Relevance
“…Bats rely on vision for long-distance orientation (23)(24)(25), are known or suspected to orient through landscapes using light cues, such as stars and postsunset glow (26,27), and use visual cues to help them find roosts in trees (28). The effects of moonlight on bat activity and fatality at turbines are not well understood, but a study in Alberta, Canada, reported higher fatality rates of silver-haired bats (Lasionycteris noctivagans) at wind turbines on nights when the moon was fully illuminated (29). There is no evidence that tree bat activity in the absence of, or distant from, turbines varies with lunar cycles or illumination (30).…”
Section: Discussionmentioning
confidence: 99%
“…Bats rely on vision for long-distance orientation (23)(24)(25), are known or suspected to orient through landscapes using light cues, such as stars and postsunset glow (26,27), and use visual cues to help them find roosts in trees (28). The effects of moonlight on bat activity and fatality at turbines are not well understood, but a study in Alberta, Canada, reported higher fatality rates of silver-haired bats (Lasionycteris noctivagans) at wind turbines on nights when the moon was fully illuminated (29). There is no evidence that tree bat activity in the absence of, or distant from, turbines varies with lunar cycles or illumination (30).…”
Section: Discussionmentioning
confidence: 99%
“…There v www.esajournals.org appears to be some degree of sexual segregation during summer, with females potentially migrating greater distances than males (Findley and Jones 1964, Cryan 2003, Cryan et al 2004. Although their distribution is unknown, the relatively high proportion of adult male hoary bat fatalities at wind energy installations in Alberta (Baerwald and Barclay 2011) suggests that more adult males move into the province than previously suspected. In Alberta, 54% of bat fatalities at wind energy installations are hoary bats (E. F. Baerwald, unpublished data).…”
Section: Study Speciesmentioning
confidence: 99%
“…We thus predicted that the isotope values in the fur of adult females are lower than those of adult males, reflecting the longer, more northern migration made by females. Based on capture and fatality records (Baerwald and Barclay 2011), we further predicted that the degree of sexual segregation, thus the difference in isotope values between males and females, is greater in hoary bats. Finally, to explore the temporal patterns of bat migration, we examined the relationship between isotope values and date.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations